Prinsip Kejujuran, Transparansi, Dan Kesederhanaan Dalam Iklan Pelayanan Publik Perspektif Hadits Nabi Muhammad SAW - Sidiq, Fajar; Alwi, Zulfahmi; Ahmad, Arifuddin; Sumai, Sumarni (STAI Bumi Silampari, 2024)
This study examines publication, promotion, in public services in the perspective of the hadith of the Prophet Muhammad SAW with a thematic hadith approach, which highlights the values ??of honesty, transparency, simplicity of information, and prohibition of fraud. This study uses a descriptive qualitative method with primary data sources from Kutubu Tis'ah and its commentary, as well as supporting literature in the form of interpretations and academic journals. The main findings indicate that relevant hadiths provide important guidelines in maintaining the integrity of information and interactions in transactions. The values ??of honesty, transparency and prohibition of fraud are not only limited to the dimensions of the buying and selling process but have direct relevance to modern public service practices. In addition, the principle of simplicity of information encourages publication and promotion of honest, accurate, and realistic services. The implementation of these principles has the potential to create a more just, transparent, and blessed public service system. This study contributes to the development of thematic hadith studies that are relevant to the dynamics of contemporary life, especially in the context of public services.